2016
DOI: 10.1515/ami-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Migratory connectivity of Golden-crowned Sparrows from two wintering regions in California

Abstract: Knowledge of migratory connectivity is critical to understanding the consequences of habitat loss and climate change on migratory species. We used light-level geolocators to determine breeding locations and migratory routes of wintering Golden-crowned Sparrows (Zonotrichia atricapilla) in two regions of California, USA. Eight out of 9 birds tagged at coastal-wintering sites in Marin County went to breeding sites along the Gulf Coast of Alaska, while 7 out of 8 inland-wintering birds in Placer County migrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(43 reference statements)
2
9
0
Order By: Relevance
“…Our findings are consistent with data from geolocator-tagged birds (Seavy et al 2012, Cormier et al 2016). These authors tagged wintering Goldencrowned Sparrows near Bolinas north of San Francisco (Marin County) and in inland central California (Placer County).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are consistent with data from geolocator-tagged birds (Seavy et al 2012, Cormier et al 2016). These authors tagged wintering Goldencrowned Sparrows near Bolinas north of San Francisco (Marin County) and in inland central California (Placer County).…”
Section: Discussionsupporting
confidence: 91%
“…Birds we recorded in inland central California sang songs of types 2, 3, or 5. Geolocator data from Cormier et al (2016) showed most of their birds that wintered in inland central California were breeding in southern Yukon or northern inland British Columbia, where song types 3, 4, and 5 are expected. however, one of those tagged birds bred near the Gulf of Alaska, where song type 2 predominates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, this individual had three longer stopovers in Alaska before proceeding to its breeding area. A similar pattern has been observed for Golden-crowned Sparrows: individuals migrating northwards along the coast to coastal breeding sites moved faster than individuals migrating to interior breeding sites (Cormier et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…The central-north Alaska breeding birds continued on their great circle route to their breeding sites while the westerly breeding individual (ID4552) turned westwards to the coast at about 54°N. This latter individual resumed migration on a coastal route, similar to that found in closely related Golden-crowned Sparrows (Zonotrichia atricapilla) wintering in coastal regions of California and breeding in similar areas in southwestern Alaska (Seavy et al 2012;Rakhimberdiev et al 2015;Cormier et al 2016).…”
Section: Discussionmentioning
confidence: 61%